Effect of Mg addition on the crystallization kinetics of Zn-Al-Cu alloys - Krupiński M.; Labisz K.; Jonda E. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this work, the main aim was to determine the effect of Mg addition on the crystallization kinetics and microstructure of Zn-10Al-1Cu alloy. The effectiveness of magnesium addition was detected on the basis of microstructure morphology investigations and changes occurring in the cooling curves of the investigated alloys. To describe the phenomena that occurred in the material during solidification under various conditions caused by a change in the chemical composition as a result of the appliance of modifiers, it was decided to use methods of thermal derivative analysis, allowing to effectively and accurately describe the crystallization kinetics of the tested materials. The scientific goal of the presented work was examination of the impact of magnesium addition and effect of the crystallization kinetics on the examined alloys. Determining the relationship between the changes in the derivative curve and the related microstructure, the influence of modifiers addition was analysed. The addition of Mg caused a shift of the solidification temperature values of phases and eutectics and monotectoid transformation (α→α’) to lower temperature values, as well as the change of the morphology of the occurring eutectic α’+η.